Quantum-Based Approach For Learning Spoken Mandarin: A Model Of Teaching Material - Tri Budianingsih (STKIP Singkawang, 2018)
This study is an of R&D (Research and Development) program which aims to produce teaching material for learning Mandarin. In producing the teaching material, this research considered the following steps: (1) analysis of needs, (2) development of teaching material (i.e. teaching material plan, product design and test (phase 1), and limited operation test (phase 2), (3) effectivity test and readability test. This research used Kemp, Borg, and Gall mixed model. This research is conducted at University of Al Azhar Indonesia (UAI), and subjected as a trial in the second-semester course. The result suggests teaching material for speaking Chinese, that is based on the quantum approach, is effective in enhancing spoken Chinese ability within students of Chinese Study Programme in UAI. The result of re-pretest in average was 77,82, whereas the result of post-test 82,12. This suggests an increase after the model is implemented as a trial. Both samples represented the normal distribution. Further, the homogeneity test revealed the number of counted F (2,25) fell under the F table (3,19). Therefore, both groups appeared to have the same variant or homogeny. On the other hand, counted t value (2,18) is higher than t table (1,73). The result indicates significant difference so as to confirm the hypothesis of this study.